IMPROVEMENT OF LIQUIDITY REGULATION TOOLS OF UKRAINIAN BANKS - Чібісова , Вікторія (Socio-economic relations in the digital society, 2019)
The importance of bank’s liquidity for achievement the efficiency of the banking system of the country is proved. The basic tools of bank’s liquidity regulation at micro and macro level are determined. Complex analysis of regulation tools is carried out, including the featuresof their use, advantages and disadvantages. The essence of rollover as a new tool of liquidity regulation on the Ukrainian banking sector is highlighted. The features of using the credit for emergency liquidity assistance (ELA) are presented. The directions of improvement of liquidity regulation tools (use of Basel III liquidity ratios and dynamic parameter of liquidity) are proposed.